The Influence of Hotel Facilities and Service Quality on Guest Satisfaction at Fave Hotel Olo Padang - Aurellia, Muthia; Hermansyah (Pt. Threeple Herphi Educate, 2025)
This study aims to examine the influence of hotel facilities and service quality on guest satisfaction at Fave Hotel Olo Padang, a prominent hospitality provider in West Sumatra, Indonesia. Utilizing a quantitative approach with a causal-associative research design, data were collected through a structured questionnaire administered to 140 guests who had stayed at the hotel. The research instrument was developed based on established indicators for each variable and validated prior to data collection. Multiple linear regression analysis was conducted using SPSS version 30. The findings reveal that while service quality has a statistically significant and positive impact on guest satisfaction (β = 0.694, p < 0.001), hotel facilities do not demonstrate a significant effect (β = -0.029, p = 0.430). However, the joint analysis using the F-test indicates that both hotel facilities and service quality together significantly influence guest satisfaction (F = 808.268, p < 0.001), explaining a substantial portion of the variance. These results suggest that although guests value the tangible aspects of the hotel environment, it is the quality of interpersonal service interactions—such as responsiveness, empathy, and reliability—that predominantly shapes their satisfaction. The study contributes to hospitality management literature by reinforcing the pivotal role of service excellence in fostering guest satisfaction, especially in mid-range hotels. Practical implications are offered for hotel managers to prioritize staff training and customer experience strategies over mere investment in physical infrastructure.